2020
DOI: 10.1002/aah.10091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Intensity of Salmincola edwardsii in Brook Trout in Northwest New Brunswick, Canada

Abstract: Parasites can compromise the health and fitness of individual fish, and it is important to generate baseline information that can then be used to document changes in the abundance and distribution of potentially pathogenic parasites. The ectoparasitic copepod Salmincola edwardsii was assessed with respect to prevalence (percentage of infected fish per site), infection intensity (number of parasites per infected fish), and attachment location on Brook Trout Salvelinus fontinalis in northwest New Brunswick, Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…All parasite species found in the present study are common in S. fontinalis inhabiting freshwater lakes and streams in northeastern North America (Frimeth 1987, You et al 2011White et al 2020) and most have been reported from other salmonid hosts in Atlantic Canada Arthur 1979, McDonald andMargolis 1995).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…All parasite species found in the present study are common in S. fontinalis inhabiting freshwater lakes and streams in northeastern North America (Frimeth 1987, You et al 2011White et al 2020) and most have been reported from other salmonid hosts in Atlantic Canada Arthur 1979, McDonald andMargolis 1995).…”
Section: Discussionsupporting
confidence: 50%
“…In southwestern Nova Scotia, emerging brook trout fry (as a cohort) acquired parasites within the first month post-emergence either through: 1) free swimming infective copepodids of S. edwardsii (see White et al 2020); 2) adult G. colemanensis transferring directly between fish (see Cusack 1988, 1989); or 3) food-borne infective stages of E. lateralis (cystacanths) and Crepidostomum sp. (metacercariae) using amphipod/mayfly larva as intermediate hosts (Baggs and Cowan 1989, Caira 1989, Shaw et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Salmincola edwardsii has a holarctic distribution and occurs in the U.K. (Fryer 1981), Greenland (Due and Curtis 1995), Iceland (Kristmundsson and Richter 2009), Norway (e.g., Stańkowska-Radziun and Radziun 1993;Amundsen et al 1997;Paterson et al 2019), Finland (Boxshall 2020), Sweden (Boxshall 2020), Germany (Boxshall 2020), Poland (Boxshall 2020), Russia (e.g., Gussev 1962Gussev , 1987Pugachev 1984;Shedko and Shedko 2002), Canada (e.g., Kabata 1988;White et al 2020), and the U.S.A. (e.g., Hoffman 1999;Ruiz et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In North America, S. edwardsii has been studied for its taxonomy and morphology (Wilson 1915;Fasten 1920;Kabata 1969;Ruiz et al 2017), attachment sites (Black 1982), reproduction (Fasten 1914), hatching, larval development and growth (Fasten 1920;Poulin et al 1990a;Curtis 1993, 1994), larval ecology (Fasten 1913;Poulin et al 1990bPoulin et al , 1991a, occurrence on wild hosts (Black et al 1983;Bertrand et al 2008;Mitro 2016;Mitro and Griffin 2018;White et al 2020) and hatchery hosts (Hare and Frantsi 1974;Duston and Cusack 2002), impact on host (Vaughan and Coble 1975;Ruiz et al 2017), and treatment (Duston and Cusack 2002). In contrast, much remains unstudied about the biology of S. edwardsii in East Asia: the species was examined only in taxonomic and faunal research in the Russian Far East (Markewitsch 1937(Markewitsch , 1956Gussev 1962Gussev , 1987Pugachev 1984;Shedko and Shedko 2002;Shedko et al 2005;Sokolov et al 2012;Busarova et al 2017) and Japan (Shedko and Shedko 2002;this paper).…”
Section: Discussionmentioning
confidence: 99%
“…In Fast East Asia, the species has been reported from southern Asian Dolly Varden in Russia (e.g., Shedko and Shedko 2002;Shedko 2005;Shedko et al 2005a, b;Sokolov et al 2012) and Japan (Shedko and Shedko 2002;Nagasawa 2020a, b;Nagasawa and Kawai 2020). In North America, this copepod is known to infect both wild and hatchery salmonids (e.g., Hare and Frantsi 1974;Black et al 1983;Duston and Cusack 2002;Mitro 2016;Ruiz et al 2017;Mitro and Griffin 2018;White et al 2020; see Nagasawa 2020a for the other literature). The col-lection of S. edwardsii in this study represents the first record of the species from captive fish in Far East Asia.…”
Section: Resultsmentioning
confidence: 99%